2023
DOI: 10.1161/circresaha.122.321858
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Ca 2+ -Dependent SK-Channel Gating and Membrane Trafficking in Human Atrial Fibrillation

Abstract: Background: Small-conductance Ca 2+ -activated K + (SK)–channel inhibitors have antiarrhythmic effects in animal models of atrial fibrillation (AF), presenting a potential novel antiarrhythmic option. However, the regulation of SK-channels in human atrial cardiomyocytes and its modification in patients with AF are poorly understood and were the object of this study. Methods and Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 72 publications
0
17
2
1
Order By: Relevance
“…To investigate the impact of SK channel modulation on atrial electrophysiology and arrhythmogenesis, we updated our established model of the human atrial myocyte in nSR and cAF conditions (41)(42)(43). We included into this cellular framework the ISK formulation that we have recently developed based on recordings in human right-atrial cardiomyocytes from nSR and cAF patients (29). To simulate INa, we used the formulation developed by Courtemanche et al (44), and adjusted its maximal conductance to maintain the physiologic AP upstroke velocity.…”
Section: Human Atrial Cardiomyocyte Simulationsmentioning
confidence: 99%
See 3 more Smart Citations
“…To investigate the impact of SK channel modulation on atrial electrophysiology and arrhythmogenesis, we updated our established model of the human atrial myocyte in nSR and cAF conditions (41)(42)(43). We included into this cellular framework the ISK formulation that we have recently developed based on recordings in human right-atrial cardiomyocytes from nSR and cAF patients (29). To simulate INa, we used the formulation developed by Courtemanche et al (44), and adjusted its maximal conductance to maintain the physiologic AP upstroke velocity.…”
Section: Human Atrial Cardiomyocyte Simulationsmentioning
confidence: 99%
“…Our default cAF model does not account for any AF-associated SK channel remodeling. However, we performed a separate set of simulations in which both SK channel conductance and Ca 2+sensitivity are altered as seen in AF (29,47).…”
Section: Human Atrial Cardiomyocyte Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The elegant article by Heijman et al 10 published in this issue of Circulation Research addressed the mechanisms of SK channel gating and membrane targeting in atrial myocytes from patients with AF, as illustrated in the Figure. Using human atrial samples from patients without a history of AF (control group) or with a clinical diagnosis of persistent AF (chronic AF [cAF] group), the authors identified the upregulation of apamin-sensitive SK currents (I SK ) in cAF atrial myocytes.…”
mentioning
confidence: 99%